Examining The Impact of Inflation on Financial Development in The Fragile Five Economies with Asymmetric Cointegration Tests - Gulcu, Yunus (Sosyoekonomi Soc, 2024)
This study examines the relationship between inflation and financial development indicators for the Fragile Five countries between 1981 and 2021. The study analysed the relationship between symmetric and asymmetric distributed lag regression models. Inflation appears to have a negative impact on financial development in countries other than Brazil and India. The results prove that the most extended correction process was experienced in India, and the shortest was experienced in Indonesia among the Fragile Five countries. Research results emphasise that high inflation negatively affects financial development in these economies by increasing the cost of financial intermediation
Kırılgan Beşli Ekonomilerinde Enflasyonun Finansal Gelişme Üzerine Etkisinin Asimetrik Eşbütünleşme Testleri ile İncelenmesi
Keywords: Financial Development; Inflation Rate; Asymmetric Cointegration